2020
DOI: 10.3390/jcm9082665
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles in Renal Patients with COVID-19

Abstract: The COVID-19 pandemic has led to frequent referrals to the emergency department on suspicion of this infection in maintenance hemodialysis (MHD) and kidney transplant (KT) patients. We aimed to describe their clinical features comparing confirmed and suspected non-confirmed COVID-19 cases during the Spanish epidemic peak. Confirmed COVID-19 ((+)COVID-19) corresponds to patient with positive RT-PCR SARS-CoV-2 assay. Non-confirmed COVID-19 ((−)COVID-19) corresponds to patients with negative RT-PCR. COVID-19 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
12
1
1
Order By: Relevance
“…The prevalence of confirmed COVID-19 in our cohort was 6.1%, lower than that described in other studies (range between 10–40%) [ 7 , 8 , 9 ]. There is a heterogeneous prevalence and mortality rate, according to different geographic areas, including within Spain [ 21 ].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The prevalence of confirmed COVID-19 in our cohort was 6.1%, lower than that described in other studies (range between 10–40%) [ 7 , 8 , 9 ]. There is a heterogeneous prevalence and mortality rate, according to different geographic areas, including within Spain [ 21 ].…”
Section: Discussioncontrasting
confidence: 83%
“…ARDS is, in part, the result of the storm of cytokines and chemo-attractant molecules that follow viral infection [ 6 ], which is aggravated by age and pre-existing conditions, including hypertension and diabetes [ 7 ]. Despite the prevalence of variable clinical presentation and outcomes in COVID-19 infected HD patients [ 8 , 9 , 10 ], the main factors driving the severity of disease progression in these specific patients remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with kidney disease, both those requiring maintenance hemodialysis and transplant recipients, are at high risk for COVID-19 and a poor outcome. Preventive measures, thus, are crucial [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 7 patients had hypophosphatemia in our study and all were experiencing severe lung injury. Arenas et al (7) study showed hypophosphatemia in renal patients with confirmed COVID-19 in comparison of renal patients who were negative for the COVID-19 PCR test. Our study is in contrast with Arenas et al as we observed a wide range of serum phosphate levels in our patients with a reasonable association with HRCT results.…”
Section: Discussionmentioning
confidence: 96%